Cognitive aspects of the philosophical and theological coherence of the concept of a miracle within the contemporary scientific world view - Wojciech Grygiel (Copernicus Center Press, 2021)
The purpose of the article is to investigate the philosophical and theological validity and coherence of the classical concept of a miracle within the contemporary scientific world view. The main tool in this process will be the cognitive standard model of the formation of religious beliefs operative in the cognitive science of religion. The application of this model shows why an intentional agent is assigned as responsible for the occurrence of events with no visible cause such as a miracle: miracles are events that violate the intuitively expected behaviors observable in the physical reality. It will become evident that much of the conceptual content of the classical understanding of miracles can be retained despite of the ontological and epistemological challenges of the contemporary science. In particular, this concerns the semantic view of miracles in which a miracle does not occur as an objective Divine intervention but qualifies as religious interpretation of the natural course of events always in reference to a cultural and personal context that is unique to those who directly experience these events either as direct recipients or as observers.